2010
DOI: 10.1097/nmd.0b013e3181fe75dc
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression, Anxiety, and Stress Among Young Male Adults in India

Abstract: The lifetime prevalence of depression, anxiety, and stress among adolescents and young adults around the world is currently estimated to range from 5% to 70%, with an Indian study reporting no depression among college going adolescents. This cross-sectional study was conducted to determine prevalence of current depressive, anxiety, and stress-related symptoms on a Dimensional and Categorical basis among young adults in Ranchi city of India. A stratified sample of 500 students was selected to be representative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 17 publications
4
85
3
3
Order By: Relevance
“…The prevalence in our study was found to be much higher when compared to various other studies, [6,9,10] where the prevalence was found to be 18.5%, 22.5%, and 21.8%, respectively, this difference could be due to increasing competition, diversity in culture, sociodemographic profile, and use of different tool. [11] Of the individuals with depression, only 1.69% were found to have severe depression score and this was in line with the document of the WHO, [4] where in the prevalence of depression ranges from 1.8% (severe) to 39.6% (mildto-moderately severe).…”
Section: Discussioncontrasting
confidence: 51%
“…The prevalence in our study was found to be much higher when compared to various other studies, [6,9,10] where the prevalence was found to be 18.5%, 22.5%, and 21.8%, respectively, this difference could be due to increasing competition, diversity in culture, sociodemographic profile, and use of different tool. [11] Of the individuals with depression, only 1.69% were found to have severe depression score and this was in line with the document of the WHO, [4] where in the prevalence of depression ranges from 1.8% (severe) to 39.6% (mildto-moderately severe).…”
Section: Discussioncontrasting
confidence: 51%
“…Studies around the world have found prevalence of depression, anxiety and stress among adolescent and young adult in the range of 5%-70%. (2) Higher education can be stressful, students have to adapt to a new lifestyle. They have to cope with various stressful situations like staying away from home, academic demands, new social relationships, and uncertainty about future.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of depression and stress varies between 15% to 40% among Indian adolescents as per different studies. [6][7][8][9] Therefore, the present study was conducted to find out the current status of mental health, prevalence and correlates of depression cum level of mood among school going adolescents.…”
Section: Introductionmentioning
confidence: 99%